Design method of magnetic resonance biplanar gradient coil based on target field method and stream function - Huang, Qingming; Huang, Luying; Zhang, Haikang; Huang, Yicheng; Wang, Wentao; Cheng, Yunzhang; Shen, Bing (Frontiers in Physics, 2025)
The gradient coil is a crucial component of the magnetic resonance imaging (MRI) system, responsible for generating linear gradient magnetic fields to facilitate spatial positioning for image reconstruction. This article combines a new target field point method and stream function with classical electromagnetism theory to design a Biplanar gradient coil. According to the demand of magnetic field strength of the gradient coil, the winding distribution characteristics of the coil are obtained by inverse simulation using numerical calculation tools. Then, a solid gradient coil model is established using electromagnetic field simulation software. The corresponding gradient magnetic field strengths are individually obtained by orthogonal analysis for the transverse gradient coil x,y, and the longitudinal gradient coil z. The gradient coil’s winding pattern is iteratively modified and optimised based on the magnetic field strength distribution. The optimisation process targets several key parameters, including gradient linearity, coil efficiency, and the uniformity of the magnetic field within the desired spherical volume (DSV). After optimisation, a prototype of the dual-plane gradient coil is fabricated and evaluated to verify its performance against theoretical expectations. The experiments show that the Biplanar gradient coil has high linearity and fast gradient switching time, and the image resolution and signal-to-noise ratio of magnetic resonance imaging is improved, which lays the foundation for high-end clinical applications such as rapid magnetic resonance imaging.